Ultrasound-based method for individualized estimation of central aortic blood pressure from flow velocity and diameter. (April 2022) - Zhou, Shuran; Yao, Yang; Liu, Wenyan; Yang, Jun; Wang, Junli; Hao, Liling; Wang, Lu; Xu, Lisheng; Avolio, Alberto
Abstract: Central aortic blood pressure (CABP) is a better predictor for cardiovascular events than brachial blood pressure. However, direct CABP measurement is invasive. The objective of this paper is to develop an ultrasound-based method using individualized Windkessel (WK) models for non-invasive estimation of CABP. Three WK models (with two-, three- and four-element WK, named, WK2, WK3 and WK4, respectively) were created and the model parameters were individualized based on aortic flow velocity and diameter waveforms measured by ultrasound (US). Experimental data were acquired in 42 subjects aged 21–67 years. The CABP estimated by WK models was compared with the reference CABP obtained using a commercial system. The results showed that the overall performance of the WK3 and WK4 models was similar, outperforming the WK2 model. The estimated CABP based on WK3/WK4 model showed good agreement with the reference CABP: the absolute errors of systolic blood pressure (SBP), 2.4 ± 2.1/2.4 ± 2.0 mmHg; diastolic blood pressure (DBP), 1.4 ± 1.1/1.7 ± 1.5 mmHg; mean blood pressure (MBP), 1.3 ± 0.8/1.3 ± 0.8 mmHg; pulse pressure (PP), 3.0 ± 2.3/3.2 ± 2.6 mmHg; the root mean square error (RMSE) of the waveforms, 2.5 ± 1.0/2.6 ± 1.1 mmHg. Therefore, the proposed method can provide a non-invasive CABP estimation during routine cardiac US examination. Highlights: This paper develops an ultrasound-based method using individualized Windkessel models for non-invasive estimation of CABP. The Windkessel model parameters were individualized from noninvasive measurements of aortic U and D waveforms by ultrasound. The performances of three Windkessel models for reconstructing CABP were compared. The central information reflecting physiological properties of the aorta is used to enhance the accuracy of CABP estimation. Our method provides CABP for assisting doctors to improve cardiovascular diagnoses during cardiac ultrasound examination.